If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x-6-2x=29
We simplify the equation to the form, which is simple to understand
7x-6-2x=29
We move all terms containing x to the left and all other terms to the right.
+7x-2x=+29+6
We simplify left and right side of the equation.
+5x=+35
We divide both sides of the equation by 5 to get x.
x=7
| 5x-3x+2=8 | | 4(9-x)=24 | | 2(2x+3)-3(x-5)=4 | | 10x-8=40x+10 | | (7x+8)=(9x-4) | | 8x-3=8(x-5) | | -4(1-3p)=-4-2(-p-5) | | x/4=11 | | 12x-83=6x+121 | | -(3x-7)=24 | | 2v-5=-10 | | (x-3)(1-x)=1 | | 3(6-x)=3 | | 12+8x-12x+6=-122 | | 4j=3.6 | | 3(y+2)+y=15-(y-4) | | 6p-6=7p-7 | | 25x+10y=405 | | 3(7-x)=12 | | 8=-4(3x-4) | | -x-6x+7=42 | | 9-3(x-4)=36 | | -62=5x+3 | | 18+2x/3=16 | | 24=(2x-3) | | 3w-3=4w+8 | | 4(7-x)=4 | | (78+x)+x=434 | | 4.9t^2-13.5t=66 | | 3n=-27 | | 4x^2+18x+14=0 | | -8+6x=38 |